Current alternatives in the prevention and treatment of xerostomia in cancer therapy - Tainara BARBIERI; Kiany Claudia da COSTA; Letícia de Freitas Cuba GUERRA (Faculdade São Leopoldo Mandic, 2020)
ABSTRACT In the last decades, there has been a substantial increase in the occurrence of cancer. The most commonly used treatment for this disease involves surgery, radiotherapy and chemotherapy. These treatment modalities are associated with different kinds of side effects, acute or late. Xerostomia is one of the main oral complications that affect patients undergoing antineoplastic treatments, mainly head and neck cancer patients. It is characterized by a "dry mouth" sensation resulting from decreased salivary flow. It is persistent and affects the integrity of oral tissues, thereby significantly affecting patients' quality of life. Many strategies have been applied and others developed to prevent and reduce xerostomia. Accordingly, the objective of this study was to review the literature about current prevention and treatment measures aimed at improving the quality of life of xerostomic patients.